Design of immunosensor for the detection of C-reactive protein using oriented antibody immobilization - Adesina, Abiola Olanike (Rhodes University, Faculty of Science, Department of Chemistry, 2020)
Early diagnosis of cardiovascular diseases (CVDs) has been a major challenge since CVDs are clinically silent. The current methods available for the diagnosis are not sensitive enough at the onset of the disease. Also, the use of sophisticated equipments and experts in the result interpretation has created a lot of barriers to the early diagnosis of CVDs. Biomarkers detection using electrochemical immunoassay offers great advantages in terms of sensitivity, miniaturization and low cost. This can be integrated into portable devices which can be made available in the remote areas for easy assessment of health care services. The fabrication of piezoelectric and electrochemical immunosensors for the detection of C-reactive protein (a cardiac biomarker) are presented in this thesis. The electrochemical immunosensor investigates the effect of linkers chain length on the analytical performance of the immunosensor. The fabricated immunosensors were based on two simple and sensitive label-free impedimetric assay. Oriented immobilization of anti-CRP monoclonal antibody (mAb) unto gold surface was achieved using carbohydrate specific boronic ester reaction for enhanced capture and specific detection of CRP protein. Quartz crystal microbalance with dissipation (QCM-D) was employed to establish the immunocomplex formation between the mAb and CRP antigen. This was achieved by forming a self-assembled monolayer (SAM) of 4-mercaptophenylboronic acid (MPBA) onto the quartz crystal surface. The limit of detection (LoD) for the direct and sandwich immunoassay was 5.45 and 3.65 ng mL-1, respectively. The Au-MPBA-mAb/glucose immunosensor with the shortest chain length of boronic acid was fabricated. The use of SAM of 4-mercaptophenylboronic acid (MPBA) afforded a thio phenylboronic acid functionalized gold surface (Au-MPBA SAM). The anti-CRP-mAb capture antibody was immobilized in an oriented manner onto gold thiophenylboronic acid to yield an Au-MPBA-mAb surface. The non-specific boronic surface was blocked using glucose to yield an Au-MPBA-mAb/glucose. The modified gold surface could detect CRP antigen. The limit of detection (LoD) was found to be 9.82 and 6.23 ng mL-1 for the direct and sandwich immunoassay; respectively. The Au-MBA-APBA-mAb/glucose immunosensor was designed by forming a SAM of 4-mercaptobenzoic acid (MBA) onto gold electrode surface. The terminal -COOH group of the MBA SAM reacted with an amino (NH2) group the 4-aminophenylboronic acid (APBA) using EDC/NHS coupling. This was followed by the immobilization of the capture antibody and the blocking of non-specific binding sites using glucose. Improved analytical parameters were obtained with LoD for the direct and sandwich immunoassays found to be 2.90 and 1.20 ng mL-1; respectively. A more stable immunosensor utilizing electrochemical grafting was investigated for the fabrication of Au-PEA-SA-APBA-mAb/glucose. The enhanced stability of the immunosensor was through the electrochemical reduction of 4-aminoethyl benzene diazonium (AEBD) salt. The surface was further derivatized with succinic anhydride to have a carboxylic derivatized surface. Carbodiimide chemistry was used to form a covalent linkage between the APBA amine group and the surface -COOH terminal group to yield an Au-PEA-SA-APBA surface. The immobilization of mAb and glucose resulted in Au-PEA-SA-APBA-mAb/glucose immunosensor. For the detection and signal enhancement, the magnetic nanoparticles conjugated with anti-CRP polyclonal antibody (pAb) was prepared. The sandwich immunoassay was used to detect CRP by the first capture at Au-PEA-SA-APBA-mAb/glucose. This was followed by signal amplification using magnetic nanoparticles coated with a silica shell and conjugated to pAb (MNP-SiO-APTES-PBA-pAb/glucose). The limit of detection was found to be 560 pg mL-1 and much lower than sandwich immunosensor fabricated using SAMS. The signal enhancement, lower detection limits and high sensitivity were obtained due to the nanoparticles for the sandwich immunoassay. The linear range for all the fabricated immunosensor ranges from 10 "“ 100 ng mL-1. The sensitivity obtained for Au-MPBA-mAb/glucose, Au-MBA-APBA-mAb/glucose, and Au-PEA-SA-APBA-mAb/glucose were 0.691, 0.885, and 11.08 kÎ©.ng-1.ml.cm-2 for the sandwich immunoassay. The piezoelectric immunosensor was regenerated using 0.1 M HCl without affecting the immobilized capture antibody. The real sample analysis was carried out in 10 % serum in a recovery study for all the fabricated immunosensor. The percentage of recovery was very close to 100 %.
Keywords: Immunochemistry; Biosensors; C-reactive protein; Immunoassay; Cardiovascular system -- Diseases